CYP2D6*2 Polymorphism as a Predictor of Failed Outpatient Tramadol Therapy in Postherpetic Neuralgia Patients. (May 2016) - Nasare, Namita Vilas; Banerjee, Basu Dev; Suryakantrao Deshmukh, Pravin; Mediratta, Pramod Kumari; Saxena, Ashok Kumar; Ahmed, Rafat Sultana; Bhattacharya, Sambit Nath
Abstract : Human cytochrome P4502D6 ( CYP2D6 ) gene is highly polymorphic, leading to wide interindividual ethnic differences in CYP2D6 -mediated drug metabolism. Its activity ranges from complete deficiency to excessive activity, potentially causing toxicity of the medication or therapeutic failure with recommended drug dosages. The aim of the study was to find the association of CYP2D6*2 polymorphisms with demographic characters (age, sex, and weight), pain intensity scales [numerical rating scale (NRS) sleep, global perceived effect (GPE)], and adverse drug effects in postherpetic neuralgia (PHN) patients receiving tramadol. The study comprised 246 patients [including 123 nonresponders (NRs) and 123 responders (Rs)] with PHN undergoing analgesic treatment at the pain clinic, Out Patient Department, University College of Medical Sciences, Guru Teg Bahadur Hospital, Delhi, India. Patients with any history of diabetes mellitus, human immunodeficiency virus, malignancy, hematological or liver disease, psychiatric illness, alcohol abuse, and tramadol sensitivity were excluded from the study. The NRSs of (resting and movement), NRS-sleep, and GPE were evaluated by the treating physician. Adverse drug effects during the time of the study were recorded. All samples were analyzed for CYP2D6*2 polymorphism using the polymerase chain reaction–restriction fragment length polymorphism method. The genotype distribution did not vary significantly among genders [NR ( P = 0.723); R ( P = 0.947)] and different age groups in NRs ( P = 0.763) and Rs ( P = 0.268). Clinically, statistically significant ( P < 0.001) results were obtained in both the groups when compared with baseline in the NRS-sleep and GPE scores, whereas no association was found between NRS-sleep and GPE scores when compared with CYP2D6*2 genotype ( P > 0.05). In addition, CYP2D6*2 genotype was not related to the adverse effects of analgesic therapy. The overall results suggested that CYP2D6*2 polymorphism plays no role in the PHN patients receiving tramadol treatment. The CYP2D6*2 polymorphism may not be a predictor of treatment outcome of patients with respect to PHN-receiving tramadol.